Profile of Acyanotic Congenital Heart Defect in Children at Dr. Soetomo General Hospital Surabaya Period of January – December 2016 - Fedora, Katherine; Utamayasa, I Ketut Alit; Purwaningsih, Sri (Universitas Airlangga, 2019)
Introduction: Acyanotic congenital heart defect is a congenital structural abnormality arising from incomplete formation of the heart or major blood vessels which generally do not interfere with the amount of oxygen or blood that reaches the body's tissues so that cyanosis are rarely found in these patients. This research aims to evaluate the profile of acyanotic congenital heart defect patients in Paediatric Cardiology Outpatient Clinic Dr. Soetomo General Hospital Surabaya period of January – December 2016 based on 4 variables; gender, age, nutritional status, type of congenital heart disease and symptoms. Until 2017, the profile of acyanotic congenital heart defect in children in Outpatient Unit of Paediatrics Department Dr. Soetomo General Hospital Surabaya has not been much researched, so this research is expected to be used as learning reference for practitioners and other readers, and also as a reference in developing management strategies for children with acyanotic congenital heart defect in the future. Methods: This was a descriptive non-experimental study using cross-sectional design and was performed by evaluating medical record of acyanotic congenital heart defect patients in Department of Paediatrics Dr. Soetomo General Hospital Surabaya period of January – December 2016 and analysed using Microsoft Excel. Results: The results of this study revealed that majority of acyanotic congenital heart defect patients were female (53.85%) with age range between 0 – <5 years old. Atrial septal defect (ASD) was the most common type of acyanotic congenital heart defect (49.8%), with sign and symptom that is commonly found in patients were failure to thrive (61.94%). Majority of patients also suffered from growth disruption with most of patients aged 0 – <5 years old are severely underweight (42.46%) and most of patients aged 5 – 18 years old are having malnutrition (38.23%).